1997
DOI: 10.1128/mcb.17.10.5935
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of AP-2 in Regulation of theR-FABPGene in the Developing Chick Retina

Abstract: Little is known regarding the molecular pathways that underlie the retinal maturation process. We are studying the regulation of the retinal fatty-acid-binding protein (R-FABP) gene, highly expressed in retinal precursor cells, to identify DNA regulatory elements and transcriptional factors involved in retinal development. Although the upstream sequence of the R-FABP gene is extremely GC rich, CpG methylation in this region is not implicated in the regulation of this gene because the 5 flanking DNA remains unm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

1998
1998
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 61 publications
0
23
0
Order By: Relevance
“…We have previously shown that AP-2␣ and AP-2␤ are specifically expressed in the amacrine and horizontal cell lineages of the developing chick retina (Bisgrove et al, 1997). Here, we describe a third member of the AP-2 family, AP-2␦, which has an even more restricted distribution pattern in the developing chick retina.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…We have previously shown that AP-2␣ and AP-2␤ are specifically expressed in the amacrine and horizontal cell lineages of the developing chick retina (Bisgrove et al, 1997). Here, we describe a third member of the AP-2 family, AP-2␦, which has an even more restricted distribution pattern in the developing chick retina.…”
Section: Discussionmentioning
confidence: 75%
“…Five AP-2 genes have been isolated in mice and humans: AP-2␣, AP-2␤, AP-2␥, AP-2␦, and AP-2⑀ (Williams et al, 1988;Moser et al, 1995;Bosher et al, 1996;Chazaud et al, 1996;Zhao et al, 2001a;Feng and Williams, 2003;Tummala et al, 2003). In chicken, two AP-2 genes have been isolated to date, AP-2␣ and AP-2␤ (Bisgrove et al, 1997;Shen et al, 1997;Bisgrove and Godbout, 1999). AP-2 proteins have a highly conserved C-terminal half, which contains the central and helix-span-helix domains involved in DNA binding and dimerization.…”
Section: Introductionmentioning
confidence: 99%
“…AP-2 expression during mouse embryogenesis was observed around the eye in areas of developing neuroepithelial sensory structures (Mitchell et al, 1991Moser et al, 1995, and AP-2a null mice exhibit a displaced optic cup with dysmorphic neural and pigmented retinal layers of the eye developing medially (Schorle et al, 1996). Recently, it was shown that AP-2 is a regulator of the retinal fatty-acid-binding protein, which is involved in the retinal maturation process (Bisgrove et al, 1997). DAP-2 expression within the region of the brain/optical lobe zone raises the question whether AP-2 is also involved in the development of the visual system.…”
Section: Expression Of Dap-2 During Drosophila Embryonic Development mentioning
confidence: 99%
“…In the carboxy-terminal half of the protein, all family members share a basic DNA-binding region, which is followed by a helix-span-helix dimerization motif through which the AP-2 proteins can form homodimers, or heterodimers with other family members (18,41,44,65,66,71). Both AP-2␣ and AP-2␤ have been linked to fatty acid-related ocular development (3,4,72). During chick retinogenesis, AP-2␣ and AP-2␤ have been shown to act as transcriptional repressors of retinal fatty acid binding protein (R-FABP), a homologue of mammalian brain FABP that is strongly expressed in the developing chick retina (3,4).…”
mentioning
confidence: 99%